Exploring the relationship between maternal parenting styles and stunting prevention behaviors in children aged 3-5 years - Arum Dwi Ningsih; Endang Yuswatiningsih; Dwi Prasetyaningati (PAGEPress Publications, 2024)
Indonesia, as a developing country, continues to grapple with various nutritional challenges, with stunting among toddlers being a significant concern. According to Nutritional Status Monitoring data from the past three years, stunting has the highest prevalence compared to other issues such as undernutrition, underweight, and obesity. Stunting reflects inhibited growth owing to insufficient nutrient intake. This study aimed to analyze the relationship between parenting styles and behaviors aimed at preventing stunting in children aged 3-5 years. Employing a correlational analysis with a cross-sectional research design, the study surveyed 128 respondents. Maternal parenting styles were assessed using questionnaires with parameters for authoritarian, democratic, and permissive approaches, while stunting prevention behaviors were evaluated using questionnaires covering cognitive, affective, and conative aspects. Analysis revealed that most respondents exhibited a democratic parenting style (52 respondents, 41%), and most demonstrated good stunting prevention behaviors (58 respondents, 45%). The Spearman test yielded a p-value of 0.000, indicating a significant relationship. Therefore, enhancing parents' understanding of proper parenting practices is crucial for preventing stunting in children aged 3-5 years.